Asymmetric impacts of economic uncertainties and energy consumption on the ecological Footprint: Implications apropos structural transformation in South Korea. (15th August 2022) - Oryani, Bahareh; Moridian, Ali; Rezania, Shahabaldin; Vasseghian, Yasser; Bagheri, Milad; Shahzad, Khuram
Graphical abstract: Highlights: The asymmetric environmental impacts of economic policy uncertainty has been verified. Data of South Korea has been used for empirical analysis. The structural transformation has added pressure on the environment. Formulating stable and transparent economic policies and law rules are recommended. Abstract: In today's globalized world, the necessity of identifying environmental drivers is more vital than ever before. An extensive literature assessment verified the environmental impact of energy use and economic growth. This study contributes to the literature by considering the inclusive environmental indicator (ecological footprint, EF), uncertainty in government policies affecting the economic decision (EPU) in the pandemic era, structural transformation (ECI), and energy consumption (EC) in South Korea. The long-run cointegration relationship among variables is confirmed through the Bayer and Hank test. However, the asymmetric relationship between EPU, EC, and ECF is verified in the short run. Moreover, the structural transformation exerts additional pressure on the short and long-term environment. Economic growth is positively linked to EF in the short run. However, it improves the environmental quality in the long run due to switching to greener energy and utilizing energy-saving technologies. Therefore, diversifying the exported products, using eco-friendly technologies in the production process, and reducing the uncertainties must prioritize designing the inclusive economic-environment national energy policy.